SUFISM AND HYBRID SPIRITUALITY - Hajam Hajam; Anwar Sanusi; Aditya Muara Padiarta (IAIN Tulungagung, 2019)
This article aims to discuss a Sufi-inspired traditional art and performance popular in Cirebon, the so-called “Brai”. The Brai is a traditional Islamic Sufism music popular among the Cirebonese. This traditional music combines sounds, lyrics, and dance that invite the practitioners and audiences to exercise the spiritual stages through music. The Brai performance follows the hierarchy of Sufi-state of minds and spiritual stages (suluk and raka’at). Thus, as this article argues, the Brai is a par excellence model for the entanglement between Islam and local culture. The Brai is indeed a way of the Cirebonese both to introduce Sufi-form of Islam and provides a performance where the profane arts and spiritual-Islamic Sufims are mutually entangled.